Systemic Administration of 8-OH-DPAT and Eticlopride, but not SCH23390, Alters Loss-Chasing Behavior in the Rat - Rogers, Robert D (Nature Publishing Group, 2013)
Gambling to recover losses is a common gaming behavior. In a clinical context, however, this phenomenon mediates the relationship between diminished control over gambling and the adverse socioeconomic consequences of gambling problems. Modeling loss-chasing through analogous behaviors in rats could facilitate its pharmacological investigation as a potential therapeutic target. Here, rats were trained to make operant responses that produced both food rewards, and unpredictably, imminent time-out periods in which rewards would be unavailable. At these decision points, rats were offered choices between waiting for these time-out periods to elapse before resuming responding for rewards (‘quit' responses), or selecting risky options with a 0.5 probability of avoiding the time-outs altogether and a 0.5 probability of time-out periods twice as long as signaled originally (‘chase' responses). Chasing behavior, and the latencies to chase or quit, during sequences of unfavorable outcomes were tested following systemic administration of the 5-HT(1A) receptor agonist, 8-OH-DPAT, the D(2) receptor antagonist, eticlopride, and the D(1) receptor antagonist, SCH23390. 8-OH-DPAT and eticlopride significantly reduced the proportion of chase responses, and the mean number of consecutive chase responses, in a dose-dependent manner. 8-OH-DPAT also increased latencies to chase. Increasing doses of eticlopride first speeded, then slowed, latencies to quit while SCH23390 had no significant effects on any measure. Research is needed to identify the precise cognitive mechanisms mediating these kinds of risky choices in rats. However, our data provide the first experimental demonstration that 5-HT(1A) and D(2), but not D(1), receptor activity influence a behavioral analog of loss-chasing in rats.